Technical analysis of power factor improvement using ETAP 12.6 at Regent Resort & Holiday Inn Canggu - Ni Made Karmiathi; I Kadek Adiana Putra (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2022)
Due to the increase of inductive load will cause a decrease in the power factor which in turn affects the distribution of electrical energy. The power factor improvement method was chosen by the Regent of Resort & Holiday Inn Canggu to meet the PLN Standard, SPLN 70-1, namely: the power factor must be > 0.85 is to install a capacitor bank. In addition to increasing the power factor, the installation of this capacitor bank is also expected to reduce power losses and voltage drops and avoid excess kVARh charges imposed by PLN. Through calculations and simulations using the ETAP 12.6 application, it is obtained that; To increase the power factor close to 0.95, 900kVAR power is required from the capacitor bank installed in LVMDP1 and LMPDP2 to compensate for the reactive power of 875.44 kVAR and 860.92 kVAR, respectively. The capacity of the capacitor bank required for LVMDP1 and LVMDP2 is 19.85 x 10-3 Farad, with a capacity value for each step of 2.20 x 10-3 Farad. By installing a capacitor bank on LVMDP1 and LVMDP2, it can increase the power factor to 0.94 and 0.95 respectively, and reduce the percentage of reactive power usage to active power to 34.3% and 34.7%.